2011
DOI: 10.1038/ng.1005
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study in Han Chinese identifies new susceptibility loci for ankylosing spondylitis

Abstract: To identify susceptibility loci for ankylosing spondylitis, we performed a two-stage genome-wide association study in Han Chinese. In the discovery stage, we analyzed 1,356,350 autosomal SNPs in 1,837 individuals with ankylosing spondylitis and 4,231 controls; in the validation stage, we analyzed 30 suggestive SNPs in an additional 2,100 affected individuals and 3,496 controls. We identified two new susceptibility loci between EDIL3 and HAPLN1 at 5q14.3 (rs4552569; P = 8.77 × 10(-10)) and within ANO6 at 12q12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 39 publications
13
127
1
3
Order By: Relevance
“…As mentioned above, combining earlier data from Lin et al . 25 with our results showed that there is no significant association of ERAP1/ERAP2 polymorphisms and the risk of AS in Chinese Han. The reason for this discrepancy is unclear, and may be due to as yet unknown environmental factors.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…As mentioned above, combining earlier data from Lin et al . 25 with our results showed that there is no significant association of ERAP1/ERAP2 polymorphisms and the risk of AS in Chinese Han. The reason for this discrepancy is unclear, and may be due to as yet unknown environmental factors.…”
Section: Discussionsupporting
confidence: 73%
“…However, our meta‐analysis of all data reported on the association of polymorphisms in these genes with AS indicated that population and geographical differences might be one of the causes of heterogeneity. Even in Asian populations, the association of ERAP1 gene polymorphisms with AS differs depending on the studied populations 25, 30, 34. Results of studies from Korea and Taiwan were similar, but different from data from mainland China.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Most previously identified genetic risk variants for AS are related to the immune response. Until recently, in a GWAS study in the Chinese Han population, Gu et al (2) discovered two new susceptibility loci rs4552569 and rs17095830 near genes (between HAPLN1-EDIL3 at 5q14.3 and within ANO6 at 12q12) related to cartilage development and bone formation. Our previous study also identified a novel single nucleotide polymorphism (SNP) site (c.4488+74 G > A) in low-density lipoprotein receptor-related protein 5 (LRP5) gene was associated with AS in the Chinese Han population (3).…”
Section: Introductionmentioning
confidence: 99%